Basil the Great’s references to Eunomius - Karolina Kochańczyk-Bonińska (Vox Patrum, 2018)
This article presents a comparative analysis of Eunomius’ Liber Apologetius and Basil of Cesarea’s Adversus Eunomium. As a result, we can discover that Basil wrote his treatise as a typical refutation and is quite precise when referring to Eunomius. Despite some omissions that can be explained basing on the structure of The Eunomian work or historical context, we can find one important omission which is strongly connected with one of the most important topics of the anti-Eunomian polemic. Although Basil pretends to comment Eunomius’ Liber Apologeticus systematically, he deliberately skips one of the most important elements of his adversary’s teaching.